Система управління екологічною безпекою автомобільного транспорту на регіональному рівні - Благой, В.В. (Культура народов Причерноморья, 2013)
Розглядаються питання впровадження і розвитку екологічної компоненти в галузях
господарювання. Вдосконалено методичне забезпечення оцінки конкурентоспроможності
автотранспортної послуги за рахунок включення оцінки екологічної безпеки перевізного процесу.
Визначаються перспективи використання цього методичного забезпечення. Рассматриваются вопросы внедрения и развития экологической компоненты в отраслях
хозяйствования. Усовершенствовано методическое обеспечение оценки конкурентоспособности
автотранспортной услуги за счет включения оценки экологической безопасности перевозочного
процесса. Определяются перспективы использования этого методического обеспечения. Considered issues of development and implementation of environmental components in the sectors of
economy. Improved methodological provision of assessment of competitiveness of the transport services by
including evaluation of environmental safety of the transport process. To determine the prospects of using this
methodological support.
The formation of public policy implementation and development of environmental components in the areas of
economic region is a strategic area of environmental policy of the regional economy, improving competitiveness
for the transition to a sustainable development strategy.
In order to effectively address the problem of continuous development and improvement of relations regarding
optimal use of resources, to vary the techniques and methods of environmental regulation policy of the regional
economy through the development of innovative methodological tools.
Methodical approach allows us to justify the nature, and to develop criteria and methodological tools of
ecological fiscal policy of regional development in order to harmonize not only economic but also ecological
relationships.
The work includes a review of the literature, which reflects the modern trends in the development of the
assessment methods to ensure the competitiveness of the trucking services.
Implementation of ecological safety management of road transport at the regional level with a clear separation
of powers will facilitate the effective implementation of the innovation and implementation of priority
environmentally directed investment programs and projects.